IMPACT OF THE TEMPERATURE-UNSPLIT SPANS ON STIFF CHARACTERISTICS OF FRAMEWORKS - Koval, P. M.; Fal, A. E.; Verovka, A. P. (Science and Transport Progress, 2010)
Natural tests of existing temperature-unsplit spans are described. The data obtained during test and theoretical computations are analyzed; the constructive factor is determined. The comparison of theoretical computations of spatial models in the LIRA SOFTWARE is carried out.